2020
DOI: 10.1101/2020.03.21.20040691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meplazumab treats COVID-19 pneumonia: an open-labelled, concurrent controlled add-on clinical trial

Abstract: Background: SARS-CoV-2 is a novel human coronavirus, there is no specific antiviral drugs. It has been proved that host-cell-expressed CD147 could bind spike protein of SARS-CoV-2 and involve in host cell invasion. Antibody against CD147 could block the infection of SARS-CoV-2. We aimed to assess the efficacy and safety of meplazumab, a humanized anti-CD147 antibody, as add-on therapy in patients with COVID-19 pneumonia. Methods: All patients received recommended strategy from Diagnosis and Treatment for 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
137
0
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(152 citation statements)
references
References 20 publications
8
137
0
7
Order By: Relevance
“…We also used primary human airway epithelial cells and the bronchial epithelial cell line (HBEC-6KT). We performed immunoblots for ACE2 and TMPRSS2 as these have been highlighted as interacting with SARS-CoV-2, while we probed CD147 as recent pre-clinical and clinical studies have provided proof of concept as a candidate SARS-CoV-2 receptor[26, 27]. Lastly, GRP78 was dominantly expressed throughout transcriptomic studies and was selected as a positive control as previous expression has been confirmed in human airway epithelial cells[58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also used primary human airway epithelial cells and the bronchial epithelial cell line (HBEC-6KT). We performed immunoblots for ACE2 and TMPRSS2 as these have been highlighted as interacting with SARS-CoV-2, while we probed CD147 as recent pre-clinical and clinical studies have provided proof of concept as a candidate SARS-CoV-2 receptor[26, 27]. Lastly, GRP78 was dominantly expressed throughout transcriptomic studies and was selected as a positive control as previous expression has been confirmed in human airway epithelial cells[58].…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence for a role of CD147 in SARS-CoV-2 binding has been demonstrated in vitro with the use of an anti-CD147 intervention that prevented virus replication[26]. Furthermore, a clinical study with an anti-CD147 intervention reduced symptoms and duration of hospital admission for COVID-19 patients[27]. In summary, although there is evidence that SARS-CoV-2 and SARS-CoV both utilize ACE2 as a receptor to facilitate virus entry, it is possible that differences in host-entry mechanisms play a role in the large epidemiological differences between the two viruses, which may include additional unidentified receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of January 2020, an extraordinary number of investigational programs and clinical trials has been initiated in a concerted effort to identify therapeutics against the rapidly growing COVID-19 pandemic. Clinical trials using repurposed clinical-stage or approved drugs such as remdesivir, favipiravir, lopinavir/ritonavir, hydroxychloroquine and others have been under investigation for treating COVID-19 patients 15,16,20,[54][55][56][57][58][59] . Some other therapies, such as treatment with antibodies from seroconverted idividuals, are also being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…3 Infection of the human cells with viral particles occurs through the binding of S viral 4 proteins to the receptors of the host cell and their subsequent priming with proteases. 5 ACE2 is considered the classic receptor for SARS-CoV-2, but there is evidence that it 6 can also use the BSG receptor (CD147) [33]. The priming of viral proteins is carried out 7 by the TMPRSS2 protease.…”
Section: Introductionmentioning
confidence: 99%
“…The exact role of BSG in COVID-19 is still 102 unknown, but recently it was found that CD147 may bind spike protein of 103 SARS-CoV-2 [33]. The preliminary data on a small sample of COVID-19 patients 104 demonstrated that Meplazumab, a humanized anti-CD147 antibody, efficiently improved 105 the recovery of patients with SARS-CoV-2 pneumonia with a favorable safety profile [6]. 106 Expression of ACE2, BSG and TMPRSS2 in single cells 107 Data on expression profiles of SARS-CoV-2-interacting genes in various tissues 108 demonstrates that ACE2 has a high level of expression only in testicles ( Fig.…”
mentioning
confidence: 99%